Customer journey in fashion industry: Online or offline - Tapadinhas, R.; Pereira, L.; Geraldes, J.; Gonçalves, R.; Dias, Á.; Lopes da Costa, R. (International Journal of Services Operations and Informatics, 2022)
Technological improvements are allowing the development of the customer experience both online and offline, and the purpose is to create a better experience. Nowadays, customers can decide to purchase products/services in two different ways: online or offline. The online experience has been changing the way companies reach the customer, while in-store experience is the traditional way of purchasing. This study analyses the customer journey and the most important attributes when the customer wants to purchase a product and must choose between the two channels in the fashion industry. It is important to understand why customers choose a channel instead of the other one, and if the combination of the two channels can improve customer experience. It used a qualitative methodology based on a set of interviews that provide results using content and cluster analysis. The main findings indicate that sensory elements are essential when customers want to purchase a clothing item and that is one of the reasons that customers, in general, prefer to purchase offline.